Fifteen new Andrena species from little-visited arid, Mediterranean, and mountainous parts of the Old World (Hymenoptera: Andrenidae) - Wood, Thomas James (Zootaxa, 2021)
Andrena is the second most speciose genus of bees, with around 1,500 species known globally. It is predominantly distributed through the Holarctic with severely limited diversity in other biogeographical regions, and with the greatest species richness in arid and Mediterranean areas. Despite a long history of study, many species remain undescribed. As part of an ongoing revision of undetermined Old World material, many new species have been discovered in museum collections. Andrena (Micrandrena) atlantea spec. nov. from Morocco, Andrena (Carandrena) hoggara spec. nov. from Algeria, Andrena (Aciandrena) plumbea spec. nov., Andrena (Carandrena) inflata spec. nov., Andrena (Chrysandrena) rubricorpora spec. nov., Andrena (Orandrena) densissima spec. nov. from Tunisia, Andrena (?Aciandrena) badiyah spec. nov., Andrena (Micrandrena) convexifrons spec. nov. from Jordan, Andrena (?Aciandrena) palmyriae spec. nov., Andrena (Graecandrena) virguladivina spec. nov., Andrena (Suandrena) inaquosa spec. nov., Andrena (Truncandrena) syriensis spec. nov. from Syria, Andrena karia spec. nov. (incertae sedis) from Turkey, and Andrena (Pallandrena) persica spec. nov. and Andrena (Pallandrena) zagrosa spec. nov. from Iran are described. The description of these 15 new species confirms the extent to which our understanding of this genus remains incomplete in the arid, Mediterranean, and mountainous parts of the Old World.